Theranostic Nanomedicines for the Treatment of Cardiovascular and Related Diseases: Current Strategies and Future Perspectives - Natasha Manners; Vishnu Priya; Abhishesh Kumar Mehata; Manoj Rawat; Syam Mohan; Hafiz A. Makeen; Mohammed Albratty; Ali Albarrati; Abdulkarim M. Meraya; Madaswamy S. Muthu (MDPI AG, 2022)
Cardiovascular and related diseases (CVRDs) are among the most prevalent chronic diseases in the 21st century, with a high mortality rate. This review summarizes the various nanomedicines for diagnostic and therapeutic applications in CVRDs, including nanomedicine for angina pectoris, myocarditis, myocardial infarction, pericardial disorder, thrombosis, atherosclerosis, hyperlipidemia, hypertension, pulmonary arterial hypertension and stroke. Theranostic nanomedicines can prolong systemic circulation, escape from the host defense system, and deliver theranostic agents to the targeted site for imaging and therapy at a cellular and molecular level. Presently, discrete non-invasive and non-surgical theranostic methodologies are such an advancement modality capable of targeted diagnosis and therapy and have better efficacy with fewer side effects than conventional medicine. Additionally, we have presented the recent updates on nanomedicine in clinical trials, targeted nanomedicine and its translational challenges for CVRDs. Theranostic nanomedicine acts as a bridge towards CVRDs amelioration and its management.